Peran Komunitas Lokal dalam Pengembangan Pariwisata Berbasis Masyarakat di Obyek Wisata Danau Kaolin - Muhammad Afif Tarjih (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to describe the role of local communities in the development of community-based tourism at Danau Kaolin tourist site, identify supporting and inhibiting factors of community involvement, and analyze its impact on tourism sustainability. The research employs a qualitative method with a descriptive phenomenological approach. Data were collected through in-depth interviews, participatory observation, and document studies involving 40 participants including local community members, tourism managers, community leaders, and local government officials. Data analysis was conducted thematically through data reduction, presentation, and conclusion drawing. The findings reveal that local communities play a central role in managing and developing tourism, especially in providing tourism services and environmental conservation. The shift in livelihoods from traditional sectors to tourism services positively impacts the community’s economic and social conditions. However, limited access to training, infrastructure, and minimal participation in decision-making are major obstacles. The novelty of this research lies in its contextual focus on Danau Kaolin as a post-mining tourism destination with unique characteristics, and the use of a phenomenological approach to deeply explore community experiences. The study implies the importance of comprehensive community empowerment and inclusive policy support to enhance the strategic role of local communities in sustainable tourism development.